Analysis of mitogen-activated protein kinase pathways used by interleukin 1 in tissues in vivo: Activation of hepatic c-Jun N-terminal kinases 1 and 2, and mitogen-activated protein kinase kinases 4 and 7 - Finch, A; Davis, W; Carter, W; Saklatvala, J (2001)
The effects of interleukin 1 (IL-1) are mediated by the activation of protein kinase signalling pathways, which have been well characterized in cultured cells. We have investigated the activation of these pathways in rabbit liver and other tissues after the systemic administration of IL-1α. In liver there was 30 - 40-fold activation of c-Jun N-terminal kinase (JNK) and 5-fold activation of both JNK kinases, mitogen-activated protein kinase (MAPK) kinase (MKK)4 and MKK7. IL-1α also caused 2 - 3-fold activation of p38 MAPK and degradation of the inhibitor of nuclear factor KB ('IκB'), although no activation of extracellular signal-regulated protein kinase (ERK) (p42/44 MAPK) was observed. The use of antibodies against specific JNK isoforms showed that, in liver, short (p46) JNK1 and long (p54) JNK2 are the predominant forms activated, with smaller amounts of long JNK1 and short JNK2. No active JNK3 was detected. A similar pattern of JNK activation was seen in lung, spleen, skeletal muscle and kidney. Significant JNK3 activity was detectable only in the brain, although little activation of the JNK pathway in response to IL-1α was observed in this tissue. This distribution of active JNK isoforms probably results from a different expression of JNKs within the tissues, rather than from a selective activation of isoforms. We conclude that IL-1α might activate a more restricted set of signalling pathways in tissues in vivo than it does in cultured cells, where ERK and JNK3 activation are often observed. Cultured cells might represent a 'repair' phenotype that undergoes a broader set of responses to the cytokine.